A high-performance approach to the strength and power training in 200m kayak/canoe - Steeves, D.; Thornley, L.; Jobin, F.; Jordan, M.; Bawol, M.; Kruk, J.; Fowles, J. R. (Journal of Australian Strength and Conditioning, 2018)
Implementing a high-performance model with an emphasis on strength and power testing and training, when the 200 m program was added to the Olympic games for canoe and kayak, supported the coach and program to achieve podium performances and maximize results on-water.